The Impact Of Instructional Technology Training And Support: A Case Study Of A Technology-Rich School - Craige, Brenda (My University, 2014)
Despite the increase in technology available to classrooms, results of the research on the impact of technology on student achievement have been mixed at best. Studies consistently show that if technology is effectively integrated into curriculum, it is much more likely to affect student learning, however, researchers have identified numerous barriers to the successful integration of technology. This qualitative case study examines the experiences of teachers, administrators, and a technology director engaged in technology implementation programs in a technology-rich school, in an effort to identify structures, conditions, and characteristics of instructional technology training and support that seem to contribute to or detract from a school’s successful implementation of technology.
Keywords: Education, Administration.